L-Theanine prevents carbon tetrachloride-induced liver fibrosis via inhibition of nuclear factor κB and down-regulation of transforming growth factor β and connective tissue growth factor. (February 2016) - Pérez-Vargas, JE; Zarco, N; Vergara, P; Shibayama, M; Segovia, J; Tsutsumi, V; Muriel, P
Here we evaluated the ability ofl -theanine in preventing experimental hepatic cirrhosis and investigated the roles of nuclear factor-κB (NF-κB) activation as well as transforming growth factor β (TGF-β) and connective tissue growth factor (CTGF) regulation. Experimental hepatic cirrhosis was established by the administration of carbon tetrachloride (CCl4 ) to rats (0.4 g/kg, intraperitoneally, three times per week, for 8 weeks), and at the same time, addingl -theanine (8.0 mg/kg) to the drinking water. Rats had ad libitum access to water and food throughout the treatment period. CCl4 treatment promoted NF-κB activation and increased the expression of both TGF-β and CTGF. CCl4 increased the serum activities of alanine aminotransferase and γ-glutamyl transpeptidase and the degree of lipid peroxidation, and it also induced a decrease in the glutathione and glutathione disulfide ratio.l -Theanine prevented increased expression of NF-κB and down-regulated the pro-inflammatory (interleukin (IL)-1β and IL-6) and profibrotic (TGF-β and CTGF) cytokines. Furthermore, the levels of messenger RNA encoding these proteins decreased in agreement with the expression levels.l -Theanine promoted the expression of the anti-inflammatory cytokine IL-10 and the fibrolytic enzyme metalloproteinase-13. Liver hydroxyproline contents and histopathological analysis demonstrated the anti-fibrotic effect ofl -theanine. In conclusion, l -theanine prevents CCl4 -induced experimental hepatic cirrhosis in rats by blocking the main pro-inflammatory and pro-fibrogenic signals.